Sustainability Awareness, Health Literacy, and the Inclination to Buy Smart Lights: A Conceptual Paper - Heqi, Zhao; Halabi, Khairun Nisa Mustaffa (South Asian Journal of Social Sciences and Humanities, 2023)
Expansion of businesses and industrialization has led to depletion of natural resources and has turned the  concerns of the global communities, especially countries like China and America, on. The excess population  of China has led to creating huge depletions of natural resources and carbon emissions. This is why China is  now considering green initiatives as compulsory and important for mitigation of negative environmental  impacts, negative impacts on the growth of economy, and on the health and literacy of the common man.  Therefore, the aim of the current study was to analyze the various factors that lead to increased opportunity of  buying from online domains. The framework presented within this study entails that social and environmental  sustainability awareness and health literacy can lead to enhancing the purchase decisions of smart and green  products such as smart light. Altruism has been used as a connection variable between these factors as  altruistic nature of consumer has shown toenhance the buying behavior. The conceptual framework presented  din this study needs to be validated through empirical research in the future.
Keywords: Altruism; Social Sustainability Awareness; Environmental Sustainability Awareness; Health Literacy; Smart Lights